Microcirculatory Differences in Children With Congenital Heart Disease According to Cyanosis and Age - González, Rafael; Urbano, Javier; Solana, María J.; Hervías, Mónica; Pita, Ana; Pérez, Rosario; Álvarez, Reyes; Teigell, Enrique; Gil-Jaurena, Juan-Miguel; Zamorano, José; Sobrino, Adolfo; López-Herce, Jesús (Frontiers in Pediatrics, 2019)
Background: Congenital heart disease (CHD) is one of the main causes of morbidity and mortality in children. Microcirculatory changes in CHD patients have been previously investigated using a variety of techniques. Handheld videomicroscopy enables non-invasive direct visualization of the microcirculatory bed. The aim of our study was to determine if there are microcirculatory differences among CHD patients based on age and presence of cyanosis. Methods: A prospective observational study was carried out. Patients with CHD undergoing corrective surgery were evaluated after anesthetic induction prior to surgery. Microcirculation was evaluated using sidestream dark field (SDF) imaging. Haemodynamics and respiratory, biochemical and tissue perfusion parameters were analyzed. Results: A total of 30 patients were included, of whom 14 were classified as cyanotic and 16 as non-cyanotic. Cyanotic patients had a higher total vessel density (p=0.016), small vessel density (p=0.004), and perfused small vessel density (p=0.013), while their microvascular flow index (MFI) was lower (p=0.013). After adjustment for age and PaO2, cyanotic patients showed increased total vessel density (p=0.023) and small vessel density (p=0.025) compared to non-cyanotic patients but there were no differences on MFI. Age was directly correlated with total MFI (spearman’s rho=0.499, p=0.005) and small vessel MFI (spearman’s rho=0.420, p=0.021). After adjustment for the type of CHD (cyanotic vs non-cyanotic) patients with MFI and small vessels MFI < 3 were younger than those with values ≥3 (p=0.033 and p=0.037). Conclusions: SDF-based evaluation of microcirculation in CHD patients showed that patients with cyanotic defects had higher vascular density, as compared to patients with non-cyanotic defects. Younger patients were more likely to have a low MFI regardless their type of CHD.